Investigation of photophysical properties and potential biological applications of substituted tris(polypyridyl)ruthenium(II) complexes - Sumitha Celin, T.; Allen Gnana Raj, G.; Prathima, T. S.; Balamurali, M. M. (Frontiers in Chemistry, 2025)
The photophysical properties of tris(polypyridyl)ruthenium(II) complex [Ru(dmbpy)3]2+ [dmbpy = 4,4′-dimethyl-2,2′-bipyridine] were investigated and compared with [Ru(bpy)3]2+ following both experimental and computational approaches. The variations in the electronic properties of the complex in the ground and excited states were determined by density functional theory (DFT) methods, and their effects on the anticancer, antioxidant, and antimicrobial activities were also evaluated by molecular docking and dynamic simulation studies. The potential of these complexes to serve as bioanalytes was investigated by their ability to bind with quinones, the well-known electron mediators in numerous light-driven reactions. Following the above, the anticancer properties were evaluated against breast cancer-related proteins. The results revealed that the complex possesses comparable anticancer and antioxidant potential to that of [Ru(bpy)3]2+. The physical, electronic, and biological properties of this complex depend on the nature of the ligands and the medium of investigation. Herein, the potential applications of [Ru(bpy)3]2+ in clinical diagnostics as antioxidants and therapeutic agents were evaluated.